Immune‐Related Adverse Events by Immune Checkpoint Inhibitors Significantly Predict Durable Efficacy Even in Responders with Advanced Non‐Small Cell Lung Cancer. (19th November 2019) - Akamatsu, Hiroaki; Murakami, Eriko; Oyanagi, Jun; Shibaki, Ryota; Kaki, Takahiro; Takase, Eri; Tanaka, Masanori; Harutani, Yuhei; Yamagata, Nao; Okuda, Yuka; Furuta, Katsuyuki; Sugimoto, Takeya; et al.
Abstract: Background: Although predictive value of immune‐related adverse events (irAEs) induced by immune checkpoint inhibitors (ICIs) have been suggested by several studies, their assessments were insufficient because patients were categorized only by the occurrence of irAEs. It has not been elucidated whether irAEs also play a significant role even in responders. Materials and Methods: Between December 2015 and September 2018, 106 patients with advanced non‐small cell lung cancer treated with ICIs were enrolled in our prospective biomarker study. Twenty‐three of these were responders, defined as those with complete or partial response. We investigated the proportion of irAEs among overall and responders. For responders, progression‐free survival (PFS) and overall survival of ICIs were compared between those with and without irAEs. As an exploratory analysis, we measured 41 proteins from peripheral blood before and after ICI treatment. Results: The proportion of irAEs was significantly higher in responders than nonresponders (65.2% vs. 19.3%, p < .01). Among responders, clinical characteristics did not differ regardless of the occurrence of irAEs. However, there was a significant difference in PFS among responders (irAE group 19.1 months vs. non‐irAE group 5.6 months; hazard ratio: 0.30 [95% confidence interval: 0.10–0.85]; p = .02). Of 41 protein analyses, fibroblast growth factor‐2 at baseline and monocyte chemoattractant protein fold change showed significant differences between them ( p < .04). Conclusion: Although this is a small sample–sized study, irAE might be a predictive factor of durable efficacy, even in patients who responded to ICIs. Investigation into the significance of irAEs in responders will contribute to the establishment of optimal administration of ICI. Implications for Practice: Although the predictive value of immune‐related adverse events (irAEs) induced by immune checkpoint inhibitors (ICIs) has been suggested by several studies, it has not been elucidated whether irAEs also play a significant role even in responders. This study showed that more than 60% of responders had irAEs. It demonstrated the strong correlation between irAEs and efficacy even in responders. Investigation into the significance of irAEs in responders will contribute to the establishment of optimal administration of ICI. Abstract : Immune‐related adverse events might be a predictive factor of efficacy, even I patients who respond to immune checkpoint inhibitor therapy. This study investigated the significance of immune‐related adverse events in patients with non‐small cell lung cancer who had complete or partial response after treatment with immune checkpoint inhibitors.